2015
DOI: 10.1007/s00604-015-1540-6
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-antibody sandwich assay for cytochrome c employing an MWCNT platform and electrochemical impedance

Abstract: We report on a sensitive aptamer-antibody interaction-based assay for cytochrome c (Cyt c) using electrochemical impedance. 4-Amino benzoic acid is used for the oriented immobilization of aminated aptamers onto multi-walled carbon nanotubes on the surface of a screen-printed electrode via electrochemical grafting. Impedance was measured in a solution containing the redox system ferro/ferricyanide. The change in interfacial charge transfer resistance (R ct ) experienced by the redox marker was recorded to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Similar strategies were also employed by replacing antibodies with aptamers. Ocaña et al reported a label-free impedimetric aptasensor for the recognition of cyt c at picomolar concentration levels based on an epoxy–graphite composite electrode. When the protein interacted with the immobilized aptamer on the aptasensor, it was detected by electrochemical impedance spectroscopy (EIS).…”
Section: Technological Applications Of Cytochrome Cmentioning
confidence: 99%
“…Similar strategies were also employed by replacing antibodies with aptamers. Ocaña et al reported a label-free impedimetric aptasensor for the recognition of cyt c at picomolar concentration levels based on an epoxy–graphite composite electrode. When the protein interacted with the immobilized aptamer on the aptasensor, it was detected by electrochemical impedance spectroscopy (EIS).…”
Section: Technological Applications Of Cytochrome Cmentioning
confidence: 99%
“…Although EIS sandwich immunoassays have previously been reported that utilize Au nanoparticles, horseradish peroxidase, and/or cytochrome c for the signal amplification , none of these studies directly compare the sensitivity obtained for direct and sandwich assays. Due to the significant difference in size between the M13 bacteriophage (MW∼16.3 MDa) and 3‐PBA (MW=214.2),one expects a much improved sensitivity for the 3‐PBA sandwich EIS immunoassay relative to the direct EIS immunoassays, and a reduction of 70× is observed for the detection limit.…”
Section: Resultsmentioning
confidence: 99%
“…Both gold- and carbon-based electrodes are commonly employed as substrates for developing electrochemical aptasensors for food safety monitoring [ 42 ]. Different approaches have been reported for the immobilization of aptamers, such as physical adsorption [ 95 , 96 ], self-assembly [ 24 , 97 , 98 ], entrapment in polymer films [ 99 ], and covalent grafting at functionalized surfaces [ 61 , 100 , 101 ] ( Scheme 1 ).…”
Section: Strategies In Electrochemical Aptasensor Design: Aptamer Immobilization and Electrochemical Signal Generationmentioning
confidence: 99%